Cryotherapy and laser treatment for acute retinopathy of prematurity: refractive outcomes, a longitudinal study. Issue 1 (1st January 1997) - Laws, Fiona; Laws, David; Clark, David
Abstract : BACKGROUND: Infants who require treatment for threshold retinopathy of prematurity are at increased risk of developing refractive errors. Following the introduction of laser treatment for threshold disease, the clinical impression was that the degree of myopia was reduced compared with cryotherapy. METHODS: A longitudinal study was carried out of refractive error at 3 and 12 months in 19 patients undergoing cryotherapy and 15 patients undergoing laser treatment. RESULTS: At 3 months the median spherical equivalent refractive error in the right eye was −3.25 dioptres after cryotherapy and +0.25 dioptres after laser therapy (similar results left eye). The median spherical equivalent refractive error in the right eye at 12 months was -5.25 dioptres following cryotherapy and -0.50 dioptres after laser (similar results left eye). There was a statistically significant difference in median spherical refractive error between the therapies at 3 months and 12 months (p<0.05 Wilcoxon rank sum) in both eyes. CONCLUSION: Laser therapy is associated with lower degrees of myopia during the first year of life, which is clinically significant in terms of visual performance and development.